Desain Pembelajaran Matematika Berbasis PMRI Pada Materi Perkalian Siswa Kelas 2 Sekolah Dasar - Wahed Dussawal; Muhammad Ihdal Husnayain; Muchlisin Muchlisin; Wulida Arina Najwa (Universitas Pendidikan Indonesia Kampus Serang, 2019)
Mathematics is one of the subjects studied by students from elementary school to university level. Therefore, mathematics becomes one of the scientific foundations at the basic level. There are some errors that are most often found in learning mathematics in the early grades of elementary school. One of them is related to understanding symbols, place values, process errors and mistakes in doing calculations. The problem is caused because the learning model provided by the teacher is still abstract. The purpose of this research is to provide alternatives learning option with to the design of realistic mathematics education learning or learning based on real life on multiplication material. This writing uses the study of literature from various scientific sources related to the problem. It is hoped that educators can apply mathematical learning models based on the Indonesian Realistic Mathematics Approach (PMRI) or RME (Realistic Mathematics Educatio) non multiplication material by using learning designs based on students' real lives or learning designs. The article shows that there is potential for PMRI design to be used to improve the multiplication ability of elementary school students.